(3OQI GdMLGd aj CSeGA GdQLGds - (3GHf GdbGVj , CHh GdYHGS CMeO Hf eMeO Hf eMeO Hf CHj GdYGajI GdecfGSj GdRfGJj, GHf GdbGVj,J (B1025 (3g` s
(3ChdgG (B:s
(3hHYO abO bUOJ HgPG GdJCdja NOeI GdEeGeg GdgGTejI hGdNRGfI GdYdejI GdefUhQjI, NRGfI Gdedc GdCYXe s
(3BNQgG (B:s
(3agPG BNQ eGMVQfG ef gPg GdYLGdI GdeHGQcI hGdMeO ddg QH GdYGdejf GfJgi ceG hLO HNW GdeDda HeHjVg ceG hLOJg hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hSde s
(3HgG JeRjbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B147s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B679 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B173 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJGQjNs